PENGGUNAAN REFUTATION TEXT ON PREZI UNTUK MEREMEDIASI MISKONSEPSI SISWA PADA MATERI SUHU DAN KALOR - Sudiarto, Satrio Putra; Tandililing, Edy; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractAbstract: This research aims to know the influence of the use of the ROTEZI (Refutation Text on Prezi) for social interactions to the lower of the number of students who experienced the misconception on the heat and temperature materials in SMA Negeri 3 Pontianak. The type of research in pseudo experiment with nonequivalent control group design. The sample in this study was XI IPA 4 as many as 37 students as experiment class and XI IPA 3 as much as 33 students as a control class. An instrument that being used in the form of multiple choice tests with open-ended rationale amounted to 9 reserved. The average percentage decrease in the number of students who have experienced the misconception on the experimental class of 52.23% while the average percentage decrease in the amount of money students are having a misconception on the control class was 43.43%. Based on the test results chi squared with a 5% significance level showed that there is a difference between the usage of Refutation Text on Prezi (ROTEZI) in social interactions with learning of conventional methods in lowering student misconceptions on the heat and temperature materials in SMA Negeri 3 Pontianak.Keywords: Misconception, prezi, refutation text, remediation, heat and temperature.